Haptics-based biometrics identity recognition system (2024)
The widespread of Internet technologies highlights one important issue. The problem is related to security and safety of our data. Traditional logins and passwords are not efficient enough and cannot guarantee expected security level. Motivated by that we present an approach to utilize haptics device (stimuli generator) within biometrics-based security procedure. The combination of these elements is based on generation of divergent stimuli and observation of the human reaction that is measured with different liveliness parameters as heart rate, emotions from the face (valence and arousal) as well as hand movements. Right now, our analysis is rather theoretical as we are still in the process of data collection. Finally, we outline further steps in the research as well as recent conclusions.